Relationship between glycosilated hemoglobin and inhibitor of plasminogen activator-1 among type 2 diabetics - Iparraguirre-López, Flor H. (2019)
The objective was to determine the relationship between the glycosylated hemoglobin level and the prevalence of type - 1 plasminogen activator inhibitor elevated in type 2 diabetic patients. The type was quantitative, design descriptive and crosssectional, 632 elderly patients were selected. 18 years, 263 men and 369 women diagnosed with type 2 diabetes, analyzed the plasma markers: PAI -1, tPA, fibrinogen and homocysteine. The status of type 2 diabetes was evaluated with HbA1c, considering itself uncontrolled patient with Hb1c values> 5.9%. Among the main results, the group of high type 2 diabetic patients (HbA1c> 5.9%) has a prevalence of 74.4% of elevated PAI-1 while patients with normal HbA1c have a prevalence of 40.7, which means that Patients who do not control their glycemic profile have 3.9 (Odd Ratio) times more risk of presenting high levels of PAI -1 in relation to patients with controlled glycemia. In addition, patients with an altered glucose profile have a 1.6 times higher risk of presenting high levels of fibrinogen and a 1.5 times higher risk of having high tPA, no association was observed between plasma homocysteine levels in uncontrolled diabetic patients, estimated with the logistic regression model. It is concluded that uncontrolled type 2 diabetic patients have an increase in the prevalence of the inhibitor of the raised type -1 plasminogen activator.